Evaluación a campo del cv. cannawine de Cannabis medicinal en Hurlingham, Buenos Aires - Guariniello, Julian; Braccini, Celina Laura; Fuentes Baluzzi, Virginia; Baldi, Emiliano; Marucco, Carla; Lewis, Silvina; Arizio, Carla Marcela (Universidad Nacional Arturo Jauretche, 2025)
Resumen extendido